2015
DOI: 10.1021/acs.jcim.5b00030
|View full text |Cite
|
Sign up to set email alerts
|

Relating Essential Proteins to Drug Side-Effects Using Canonical Component Analysis: A Structure-Based Approach

Abstract: The molecular mechanism of many drug side-effects is unknown and difficult to predict. Previous methods for explaining side effects have focused on known drug targets and their pathways. However, low affinity binding to proteins that are not usually considered drug targets may also drive side-effects. In order to assess these alternative targets, we used the 3D structures of 563 essential human proteins systematically to predict binding to 216 drugs. We first benchmarked our affinity predictions with available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…We evaluated the physical features of the predicted structure sites and the degree to which they shared similarity with the experimental structure sites. We previously developed PocketFEATURE (PF), an algorithm that evaluates similarity between two functional sites in terms of their physicochemical features . As part of this work, we applied the PF algorithm to assess the extent to which physicochemical features that are observed in experimental structures can be replicated by predicted structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the physical features of the predicted structure sites and the degree to which they shared similarity with the experimental structure sites. We previously developed PocketFEATURE (PF), an algorithm that evaluates similarity between two functional sites in terms of their physicochemical features . As part of this work, we applied the PF algorithm to assess the extent to which physicochemical features that are observed in experimental structures can be replicated by predicted structures.…”
Section: Introductionmentioning
confidence: 99%
“…We previously developed PocketFEATURE (PF), an algorithm that evaluates similarity between two functional sites in terms of their physicochemical features. [9][10][11][12] As part of this work, we applied the PF algorithm to assess the extent to which physicochemical features that are observed in experimental structures can be replicated by predicted structures. We also analyzed features of quaternary structure assemblies in two oligomeric proteins and disease-causing variants, which often play an important role in protein function.…”
mentioning
confidence: 99%
“…Although, target essentiality (the target protein is essential in nature) is claimed to play lead role in drug side effects (Wang et al. 2013a, 2013b; Liu and Altman 2015), we observed that the variation in evolutionary rates between SET and NSET proteins does not solely depend on target essentiality. We also used three druggability measures of targets: (i) total druggability, essential druggability, and killer druggability to explain the rate discrepancy of SET vs. NSET proteins.…”
Section: Introductionmentioning
confidence: 72%
“…Competitive binding of Mdr1-modulating drugs may prevent Mdr1’s interaction with its typical substrates, leading to adverse effects. To investigate the possible role of human Mdr1 in regulating anxiety-related behaviors, we used an established analytical approach (Liu and Altman, 2015, Lounkine et al, 2012) to calculate Mdr1’s enrichment factor (EF) against each of 10,098 possible human adverse drug reactions (ADRs) gathered from the OFFSIDES collection of FDA drug reports (Tatonetti et al, 2012); Figure 6A). …”
Section: Resultsmentioning
confidence: 99%